Pengaruh Dukungan Psikososial terhadap Penyesuaian Diri Siswa dalam Pendidikan Inklusif - Lase, Justin Foera-era (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Inclusive education requires elementary schools to create learning environments that accommodate diverse student needs, particularly in supporting students’ self-adjustment within the school setting. Psychosocial support is a crucial factor as it contributes to students’ sense of security, social acceptance, and emotional well-being. This study aims to examine the effect of psychosocial support on students’ self-adjustment in an inclusive education context. A quantitative approach with a correlational research design was employed. The sample in this study was selected using a quota sampling technique, consisting of 45 fifth-grade students who participated in inclusive education services at SD Negeri 078524 Iraono Lase. Data were collected using psychosocial support questionnaires and student self-adjustment scales and were analyzed through simple regression analysis. The results indicate that psychosocial support has a positive and significant effect on students’ self-adjustment, reflected in improved social interaction skills, emotional regulation, and adaptation to school demands. These findings highlight the importance of strengthening psychosocial support provided by teachers, counselors, and the school environment as a key strategy for enhancing the effectiveness of inclusive education practices in elementary schools.